2019
DOI: 10.21815/jde.019.114
|View full text |Cite
|
Sign up to set email alerts
|

Use of Digital Technology to Improve Objective and Reliable Assessment in Dental Student Simulation Laboratories

Abstract: The aim of this study was to assess inter‐and intra‐grader agreement with the use of digital scanning and a tooth preparation assessment software program in comparison to the current traditional visual grading method in a dental student simulation laboratory. Students' typodont teeth preparations from previous practical examinations were used (cast crown n=50; cast fixed partial denture abutments n=50). Five preclinical instructors received calibration training and evaluated each of the preparations by the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 39 publications
(49 reference statements)
0
23
0
Order By: Relevance
“…Especially in the field of motor skills training, digital software tools can be used to evaluate the manual abilities of potential candidates for the dental curriculum, to analyze students' preclinical preparations, to enable self-assessment, and to enhance the quality of education. The objective and exact nature of these digital evaluations helps to improve students' visualization, provides immediate feedback, and enhances instructor evaluation and student self-evaluation and self-correction [43,94]. Students can learn to self-assess their work with self-reflection and faculty guidance in conjunction with a specially designed digital evaluation tool [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially in the field of motor skills training, digital software tools can be used to evaluate the manual abilities of potential candidates for the dental curriculum, to analyze students' preclinical preparations, to enable self-assessment, and to enhance the quality of education. The objective and exact nature of these digital evaluations helps to improve students' visualization, provides immediate feedback, and enhances instructor evaluation and student self-evaluation and self-correction [43,94]. Students can learn to self-assess their work with self-reflection and faculty guidance in conjunction with a specially designed digital evaluation tool [48].…”
Section: Discussionmentioning
confidence: 99%
“…Visual inspection of students' work is known to have shortcomings in inter-and intra-examiner reliability, whereas standardized digital surface mapping of abutment tooth preparations facilitates objective evaluation and feedback (Table 2) [34][35][36][37][38][39][40][41][42][43][44][45][46]. In the preclinical training of dental students, the use of software that can match the student's scanned preparation with an ideal tooth preparation has been proven to be a helpful tool in the evaluation of preparation form, taper, and substance removal.…”
Section: Digital Surface Mappingmentioning
confidence: 99%
“…Additionally, some studies have reported usefulness of the digital educational device from standpoints of objective assessment. 8 , 9 , 10 , 11 , 12 , 13 Thus, the digital simulator would hold the promise of its great potential in dental education, however, it has not yet been widespread in dental schools in the world. 1 Majority is still the conventional simulator training, in which trainees cut artificial teeth attached on phantom head and teachers perform visual inspection to make assessment and instruction.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, a recent study by Miyazono et al [62] shows that purely examiner-based evaluation was associated with significantly higher inter-rater disagreement. A complementary use of evaluation software would increase objectivity and reliability.…”
Section: Discussionmentioning
confidence: 93%